Verbal School at Alapaevsky Plant (1735—1744) - A. M. Safronova (Научный диалог, 2022)
The history of the organization of the verbal school at the Alapaevsky factory, where children from the Sinyachikhinsky and Susansky factories, located 10 and 16 versts from it, were studied. The results of the children census in 1734, who lived in the territory of factory settlements and ascribed settlements, are disclosed. Based on the formation of an information base about students, the social and age composition of the students of the Alapaevskaya school was analyzed, all the main and additional admissions of children to school in 1735—1742 were identified. It has been established that in 1742 138 children were taught to read and write by the exiled Ivan Belyaev. The methods of teaching literacy are described. It is reported about the escapes of students from school, about the attempts of parents of raznochintsy, assigned to factories, to free their children from education in connection with the need to pay a chevage. The fate of students is traced: group transfers to an arithmetic school, where 72 % of children who have mastered literacy continued their education, the distribution of some of the underachieving and “age” students “to work” until the end of their studies. The consequences of chronic overspending of funds entitled for the activities of schools by the factory states in 1735 are revealed. The question was raised about the need to study the events of the last two years of the school’s activity, as well as the life of 50 of its students, who began teaching literacy in 1741—1742.